PENGELOLAAN KELAS DALAM PENDIDIKAN INKLUSI DALAM UPAYA MENINGKATKAN MOTIVASI ANAK DI TK MUTIARA BUNDA CILEGON - Zharifah Dzakir; Umayah Umayah; Teguh Fachmi; Lina Rahayu (Jurnal Anak Bangsa, 2024)
This research is based on the fact that many children in Mutiara Bunda Kindergarten Cilegon are not yet optimal when learning. This research aims to determine (1) Management of Inclusive Classes (2) Providing Learning Motivation to Children with Special Needs. This research uses descriptive qualitative methods, data obtained from observation, documentation, interviews and triangulation. In this study, the research subjects were 4 class teachers, 3 accompanying teachers, 3 children with special needs, and 2 regular children. Data analysis includes data reduction and data presentation as well as drawing conclusions. The results of this research show that, (1) The teacher's strategy or method for managing inclusive classes. (2) the way accompanying teachers provide learning motivation to children with special needs can have a positive impact, the children feel happy, so that it can make the learning and teaching process easier. Providing rewards has been proven to increase children's learning motivation at Mutiara Bunda Kindergarten, Cilegon